(untitled) (New Delhi, 2015)
This book is intended as a reference guide for graduate students, postgraduate students and researchers with a basic knowledge of protein chemistry who would like to know more about the biomedical applications of natural proteins to promote healthier lives. The book is divided into ten chapters, each of which explains different natural proteins and their established biomedical applications. The first chapter extensively deals with protein based natural fibers and provides an overview of all protein based fibers currently available.℗ℓ In turn, chapter two mainly focuses on the biomedical applications of a special class of proteins called Heat Shock Proteins; the biomedical applications of silkworm pupae proteins are dealt in chapter three. Chapter four examines an interesting use of Eri silk fibroin as a biomaterial for Tissue Engineering, while chapter five discusses the key experimental details involved in converting Tasar silk sericin into self-assembled nanoparticles. Chapter six offers brief descriptions of bioactive proteins with respect to their sources, synthesis and applications. Chapter seven is dedicated to Interleukine-8 and its role in human life, while chapter eight addresses the importance of natural proteins in infectious diseases. Chapter nine explores the issue of excess intake of dietary proteins and its adverse effects, and finally, chapter ten discusses the efficiency of drug delivery systems made up of gelatin nanocomposites. The book is above all intended as a valuable resource for students and researchers alike, sparking their curiosity with regard to the applications of natural proteins and motivating them to focus their own energies on the discovery or identification of additional natural proteins for diverse biomedical uses.
Keywords: Protein,Biomedical engineering,Proteins,Công nghệ y sinh; Công nghệ sinh học,Biotechnology